2016
DOI: 10.14814/phy2.12965
|View full text |Cite
|
Sign up to set email alerts
|

Increased hemoglobin-oxygen affinity ameliorates bleomycin-induced hypoxemia and pulmonary fibrosis

Abstract: Although exertional dyspnea and worsening hypoxia are hallmark clinical features of idiopathic pulmonary fibrosis (IPF), no drug currently available could treat them. GBT1118 is a novel orally bioavailable small molecule that binds to hemoglobin and produces a concentration‐dependent left shift of the oxygen–hemoglobin dissociation curve with subsequent increase in hemoglobin–oxygen affinity and arterial oxygen loading. To assess whether pharmacological modification of hemoglobin–oxygen affinity could ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…It is also remarkable that the Bohr effect (shifting of the dissociation curve as blood CO 2 /pH increases/decreases) applies to mammalian blood with a magnitude range that also closely follows a heterogonic relationship (Riggs, 1960 ), a factor that could further amplify the human-mouse difference, particularly when CO 2 increases during obstructive apneas are taken into account (Farré et al, 2007 ). Interestingly, the earlier reports on detectable differences among hemoglobin dissociation curves in human and mouse blood have been subsequently confirmed as measurement techniques have improved (Gray and Steadman, 1964 ; Severinghaus, 1979 ; Mouneimne et al, 1990 ; Geng et al, 2016 ). Figure 1 (top) clearly shows that for any given SaO 2 value, PaO 2 is always lower for human than for mouse blood.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…It is also remarkable that the Bohr effect (shifting of the dissociation curve as blood CO 2 /pH increases/decreases) applies to mammalian blood with a magnitude range that also closely follows a heterogonic relationship (Riggs, 1960 ), a factor that could further amplify the human-mouse difference, particularly when CO 2 increases during obstructive apneas are taken into account (Farré et al, 2007 ). Interestingly, the earlier reports on detectable differences among hemoglobin dissociation curves in human and mouse blood have been subsequently confirmed as measurement techniques have improved (Gray and Steadman, 1964 ; Severinghaus, 1979 ; Mouneimne et al, 1990 ; Geng et al, 2016 ). Figure 1 (top) clearly shows that for any given SaO 2 value, PaO 2 is always lower for human than for mouse blood.…”
mentioning
confidence: 89%
“…SaO 2 and PaO 2 : arterial oxygen saturation and partial pressure, respectively. The dissociation curves for human and mouse blood were redrawn from data in Severinghaus ( 1979 ) and Geng et al ( 2016 ), respectively. (Bottom) Relationship between equivalent (same PaO 2 ) values of SaO 2 in human and mouse blood.…”
mentioning
confidence: 99%
“… 5 , 6 In addition, increasing the Hb–O 2 affinity may benefit hypoxemia related to pulmonary diseases as it will increase O 2 saturation in the lungs. 7 , 8 Alternatively, decreasing Hb–O 2 affinity could be useful in diseases such as tumor hypoxia, wound healing, or ischemia where increased O 2 delivery to tissues is needed. 1 For these reasons, various Hb modifiers have been identified that either increase (5-HMF, tucaresol, BW12C, voxelotor [previously known as GBT440], GBT1118) or decrease (RSR-13, ITPP) Hb–O 2 affinity.…”
Section: Introductionmentioning
confidence: 99%
“… 1 For these reasons, various Hb modifiers have been identified that either increase (5-HMF, tucaresol, BW12C, voxelotor [previously known as GBT440], GBT1118) or decrease (RSR-13, ITPP) Hb–O 2 affinity. 5 , 7 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Voxelotor is oral, once-daily drug that binds to the α-chain of HbS, stabilizing the molecule in the R-state conformation, which is known to interrupt HbS polymerization. 101,165,166 The target for HbS modification with voxelotor is 20%-30%. In phase 1/2 trials, Voxelotor inhibited HbS polymerization, RBC sickling, and hemolysis, with a consequent increase in Hb concentration, while also demonstrating an acceptable safety profile and was well tolerated.…”
Section: Ementioning
confidence: 99%